Another Montaigne: Imagining an Atomic Afterlife. Issue 1 (2nd January 2018) - Gray, Alex
Abstract : Montaigne's annotations on his copy of Lucretius's poem De rerum natura reveal that he immerses himself in Lucretius's world of atoms to the point of toying with the idea of a future version of himself, 'alius montanus'. Montaigne imagines that this future self would be formed centuries after his death from the same atoms which constitute his current self. Whilst the Essais are certainly concerned with posterity and the survival of Montaigne's identity and personality through the text, Montaigne's annotations on his Lucretius privately consider an alternative legacy and a different kind of afterlife. This is not so much a question of being remembered by posterity as much as it is Montaigne imagining his own posterity. As Montaigne casts himself into the future, he contemplates whether this future self would be consubstantial with his present self in the way that he envisages the Essais to be. The Essais provide a repository of memory and personal experiences from which a reader can reconstruct Montaigne, but is it possible that the atoms forming a future Montaigne would transmit these memories and experiences which are essential to a reconstruction of his identity and self?